A Genome-Wide Characterization of the Xyloglucan Endotransglucosylase/Hydrolase Family Genes and Their Functions in the Shell Formation of Pecan - Mengyun Wen; Zekun Zhou; Jing Sun; Fanqing Meng; Xueliang Xi; Aizhong Liu; Anmin Yu (Horticulturae)
Xyloglucan endotransglucosylases/hydrolases (XTHs) are key enzymes involved in cell wall remodeling by modifying xyloglucan–cellulose networks, thereby influencing plant growth, development, and secondary cell wall formation. While the roles of XTHs have been extensively studied in primary and secondary growth, their functions in the formation and thickening of lignified nut shells remain largely unknown. Pecan (Carya illinoinensis), an economically important nut crop, develops a hard, lignified shell that protects the seed during fruit maturation. In this study, we performed a comprehensive genome-wide characterization of the XTH gene family in pecan and identified 38 XTH genes, which were categorized into four distinct phylogenetic groups. Structural analyses of the deduced proteins revealed conserved catalytic residues alongside divergent loop regions, suggesting functional diversification. Expression profiling across various tissues and among pecan cultivars with contrasting shell phenotypes indicated that specific XTH genes may play critical roles in shell structure formation. Moreover, gene regulatory networks in thin- and thick-shelled pecans provided new insights into the molecular mechanisms underlying shell development and thickness regulation. These findings lay a foundation for future genetic improvement strategies targeting nut shell traits in woody perennials.